The Impact of Qatari Measures during the Covid-19 Crisis on Peaceful Coexistence in the State of Qatar in light of the Goals of the Alliance of Civilizations - Al-Hammadi, Hind Mohammad Ahmed (Dirasat: Human and Social Sciences, 2024)
Objectives: This field study aims to identify the extent of peaceful coexistence that has been achieved among population groups in the State of Qatar through the Qatari health and precautionary measures during the pandemic in the years 2020-2021, and the extent of the expatriates’ satisfaction with these measures, and their influence on supporting stability and peaceful coexistence. Methods: This empirical study relied on the descriptive analytical approach, a questionnaire tool and a sample of (2401) persons to collect information, classify and analyze it to reach results that may benefit those interested in issues of population diversity and peaceful coexistence by taking advantage from the Qatari experience to preserve the rights of migrants and the goals of the Alliance of Civilizations. Results: The study came out with a set of results, like having a high satisfaction rate of 90.7% about the Qatari measures, and recommends taking advantage of the Qatari measures during the pandemic to deal with other global crises. Conclusions: Studying issues of peaceful coexistence is one of the important studies that overshadow world peace, and this study is a model to be followed to prevent tensions and conflicts during emergency crises, protect human rights and achieve the goals of the Alliance of Civilizations.